The SMAC Mimetic APG-1387 Sensitizes Immune-Mediated Cell Apoptosis in Hepatocellular Carcinoma - Chen, Zide; Chen, Jiehua; Liu, Hongyan; Dong, Wei; Huang, Xuan; Yang, Dajun; Hou, Jinlin; Zhang, Xiaoyong (Frontiers in Pharmacology, 2018)
The inhibitor of apoptosis protein (IAP) genes are frequently overexpressed in malignancies. Second mitochondria-derived activator of caspase (SMAC) mimetics, which target IAPs, have potential to trigger cancer cell death and sensitize tumor cells to cytotoxic therapy. The aim of this study was to investigate the anti-tumor potential of a novel bivalent SMAC mimetic, APG-1387, in hepatocellular carcinoma (HCC). The mRNA and protein expressions of IAPs, including cellular IAPs (cIAP1 and cIAP2) and X chromosome-linked IAP (XIAP), were increased in HCC tumors compared with normal liver tissue. APG-1387 treatment alone significantly reduced the protein levels of IAPs, but had only a modest effect on the viability and apoptosis of HCC cells in vitro. However, APG-1387 in combination with tumor necrosis factor-alpha (TNF-α) or tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) significantly reduced cell viability and proliferation, and induced apoptosis in HepG2 cells, as well as in HCCLM3 cells that harbors cancer stem cell-like properties. These synergistic killing effects were caspase-dependent and partially dependent on RIPK1 kinase activity. Furthermore, APG-1387 also promoted the killing effect of Natural Killer cells on HCC cells in vitro and the combination therapy significantly inhibited tumor growth by inducing cell apoptosis in xenograft mice model. In conclusion, our study clarified that APG-1387 could sensitize HCC cells to cytokines or immune cells mediated cell killing and implied that potential of SMAC mimetic based combination immunotherapy for HCC treatment.